Assessing the utility of routine viral surveillance performed in children undergoing autologous stem cell transplantation at a single centre. Issue 12 (21st September 2022) - Foley, David A.; Wong, Jessica Win See; Keane, Aoife; Ramachandran, Shanti; Blyth, Christopher C.; Yeoh, Daniel K.
Abstract: We assessed the utility of routine viral surveillance for cytomegalovirus, Epstein–Barr virus and human adenovirus in children <16 years, undergoing autologous stem cell transplantation (ASCT) at a single centre over a 10‐year period. A total of 85 ASCT were performed in 65 patients. Routine viral surveillance resulted in a high number of tests performed (median 20 tests per ASCT), without any clinically significant viral detections. These data support the limited clinical utility of routine viral surveillance in children undergoing ASCT. Adopting a clinically driven approach for viral testing is likely to be both cost‐effective and safe.